Investigating the element distribution of argumentative essay and its quality: The case of Indonesian EFL students - Rahmadi Nirwanto; Nur Mukminatien; Nunung Suryati; Anik Nunuk Wulyani (Universitas Islam Negeri Palangka Raya, Indonesia, 2024)
Although many research studies discussed argumentative essays, little is known about argumentative essays discussing the dialogical exchange of argumentation. This study aims to investigate the distribution of elements and the quality of argumentative essays produced by EFL students. The content analysis was employed to examine their argumentative essays. The data were garnered from essay writing tests for forty students of the English Department at a state university in Palangka Raya, Indonesia. They were assigned to write an argumentative essay about